Deubiquitination of ELK-1 by USP17 regulates its transcriptional potency and cell proliferation - Ducker, Charles (2018)
The transcription factor ELK-1 is associated with numerous cellular processes, notably in cell proliferation and lineage determination. ELK-1 forms a ternary complex with a dimer of Serum Response Factor at Serum Response Elements associated with immediate-early genes, such as CFOS. Following mitogen-stimulated activation of the ERK cascade, ELK-1 is phosphorylated to mediate transcriptional activation of its target genes. Further to phosphorylation, ELK-1 is covalently modified post-translationally with both monoubiquitin and polyubiquitin chains. This study sought to understand the functional significance and regulation of ELK-1 ubiquitination. Sites of ubiquitination of ELK-1 ectopically expressed in HEK293T cells were mapped and screened for the signature diglycine motif associated with ubiquitinated tryptic peptides using liquid chromatography - tandem mass spectrometry (LC-MS/MS). This revealed that lysine residues within the amino-terminal DNA-binding domain of ELK-1 are monoubiquitinated, including those involved in DNA binding.